Α1-Antitrypsin deficiency · 5: Intravenous augmentation therapy: current understanding. Issue 8 (28th July 2004) - Stoller, J K; Aboussouan, L S
Abstract : The biochemical and clinical efficacy of intravenous augmentation therapy in α1 -antitrypsin deficiency is reviewed, adverse events experienced with this treatment are considered, and its cost effectiveness is discussed.